Gingival crevicular fluid adrenomedullin level in individuals with and without diabetes mellitus type 2. (8th October 2012) - Ertugrul, A. S.; Dikilitas, A.; Sahin, H.; Alpaslan, N. Z.; Bozoglan, A.
<x xml:space="preserve">Abstract</x> Background and Objective Adrenomedullin, an antimicrobial peptide, has biological applications in many tissues, but its main attribute is its ability to lower arterial pressure. The plasma adrenomedullin level is elevated in pathophysiological conditions such as arterial hypertension, acute coronary syndrome, renal diseases, diabetes mellitus and periodontal diseases. The aim of this study was to compare the amounts of adrenomedullin in the gingival crevicular fluid of periodontally healthy individuals, individuals with chronic periodontitis, periodontally healthy individuals with diabetes mellitus type 2 and individuals with chronic periodontitis and diabetes mellitus type 2. Material and Methods Eighty‐four individuals were included in this study: 21 periodontally healthy individuals; 21 individuals with chronic periodontitis; 21 periodontally healthy individuals with diabetes mellitus type 2; and 21 individuals with chronic periodontitis and diabetes mellitus type 2. An ELISA was performed to measure the adrenomedullin levels in gingival crevicular fluid. Results Groups with diabetes mellitus type 2 (periodontally healthy individuals and individuals with chronic periodontitis) had significantly higher periodontal clinical indices than did nondiabetes mellitus groups (periodontally healthy individuals and individuals with chronic periodontitis). The group of individuals with chronic periodontitis and diabetes mellitus type 2 had a significantly higher total adrenomedullin level compared with the other groups. Also, a significantly higher total adrenomedullin level was found in diabetes mellitus type 2 groups (periodontally healthy individuals and individuals with chronic periodontitis) compared with nondiabetes mellitus groups (periodontally healthy individuals and individuals with chronic periodontitis). Conclusions An increased adrenomedullin level was found in individuals with chronic periodontitis and also in individuals with diabetes mellitus. It is thought that the effect of diabetes mellitus on the pathogenesis of chronic periodontitis could have been achieved through antimicrobial peptides such as adrenomedullin, or that increased adrenomedullin was released in individuals with diabetes mellitus in order to ensure no further periodontal tissue loss.